2008
DOI: 10.1111/j.1365-2222.2008.03071.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐13 induced increases in nitrite levels are primarily driven by increases in inducible nitric oxide synthase as compared with effects on arginases in human primary bronchial epithelial cells

Abstract: . IL-13 induced increases in nitrite levels are primarily driven by increases in inducible nitric oxide synthase as compared with effects in arginases in human primary bronchial epithelial cells. Clin Exp Allergy 2008; 936-46.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 0 publications
6
34
0
2
Order By: Relevance
“…There were previously reported that OVA increased the breathing resistance of the mice [11], resistive breathing induced IL-4 expression in diaphragm muscle [12], Th2 cytokines such as IL-4 and IL-13 induce iNOS expression through the STAT-6 pathway [13][14][15][16][17], iNOS reduced diaphragm muscle contraction, inhibition of iNOS induction and inhibition of NOS activity prevented diaphragm muscle contractile dysfunction [18]. Study results of ours are in agreement with study that previously reported.…”
Section: Discussionsupporting
confidence: 83%
“…There were previously reported that OVA increased the breathing resistance of the mice [11], resistive breathing induced IL-4 expression in diaphragm muscle [12], Th2 cytokines such as IL-4 and IL-13 induce iNOS expression through the STAT-6 pathway [13][14][15][16][17], iNOS reduced diaphragm muscle contraction, inhibition of iNOS induction and inhibition of NOS activity prevented diaphragm muscle contractile dysfunction [18]. Study results of ours are in agreement with study that previously reported.…”
Section: Discussionsupporting
confidence: 83%
“…Endobronchial tissue for immunohistochemistry (IHC) was collected at all the SARP sites listed above, whereas tissue and epithelial cell samples for mRNA were collected only at the National Jewish Health and then the University of Pittsburgh site. Epithelial cells were obtained by brushing the proximal airways as previously described (28). The cells were placed in Trizol (Invitrogen, Carlsbad, CA) for extraction of mRNA.…”
Section: Bronchoscopy Bal and Sample Processingmentioning
confidence: 99%
“…These procedures were performed across sites according to previously published protocols and the SARP manual of procedures (4,6,27,28). Endobronchial tissue for immunohistochemistry (IHC) was collected at all the SARP sites listed above, whereas tissue and epithelial cell samples for mRNA were collected only at the National Jewish Health and then the University of Pittsburgh site.…”
Section: Bronchoscopy Bal and Sample Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Its inhibition in vivo by biologic therapies targeted toward IL-4 and -13 confirms its association with this immune pathway (14)(15)(16)(17). However, FE NO elevation is observed across a range of disease states, including a high-risk asthma phenotype, CS refractory asthma, and even atopy without asthma (18,19).…”
mentioning
confidence: 99%